2021
DOI: 10.21037/atm-21-981
|View full text |Cite
|
Sign up to set email alerts
|

In vivo CT imaging of gold nanoparticle-labeled exosomes in a myocardial infarction mouse model

Abstract: Background: Acute myocardial infarction (MI) is the primary factor leading to cardiovascular diseases, which are the main causes of morbidity and mortality in developed countries. Mesenchymal stem cell (MSC)-derived exosomes have been reported to improve heart function after MI; however, the molecular mechanisms responsible for this are unknown. In vivo imaging can reveal the trafficking process and in vivo biodistribution of exosomes, which may provide an insight into the communication mechanisms and pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The induction of the AMI was performed as described previously [ 34 ]. Briefly, following anesthetization with 2% isoflurane, the heart was exposed through a small chest incision, and the left main descending coronary artery (LCA) was located and permanently ligated with a 7-0 silk suture 2-3 mm from the origin of the left atrium.…”
Section: Methodsmentioning
confidence: 99%
“…The induction of the AMI was performed as described previously [ 34 ]. Briefly, following anesthetization with 2% isoflurane, the heart was exposed through a small chest incision, and the left main descending coronary artery (LCA) was located and permanently ligated with a 7-0 silk suture 2-3 mm from the origin of the left atrium.…”
Section: Methodsmentioning
confidence: 99%
“…Other detection methods involving plasmonic nanomaterials have also been reported [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. One of these methods is to use cantilever arrays to respond to the molecular binding of multiple targets [ 100 ].…”
Section: Plasmonic Nanostructuresmentioning
confidence: 99%
“…The application forms are diverse, including local injection, smearing, exosome-loaded scaffolds, etc. Gong et al (2021) performed intramyocardial injection of gold nanoparticle-labeled exosomes in a myocardial infarction mouse model. In vivo CT imaging showed that majority of MSC-Exos remained in the MI area for up to 24 h after injection, and only few spread to other organs, indicating local injection as an effective way to deliver exosomes to limited treatment areas (Gong et al, 2021).…”
Section: Topical Administrationmentioning
confidence: 99%
“… Gong et al (2021) performed intramyocardial injection of gold nanoparticle-labeled exosomes in a myocardial infarction mouse model. In vivo CT imaging showed that majority of MSC-Exos remained in the MI area for up to 24 h after injection, and only few spread to other organs, indicating local injection as an effective way to deliver exosomes to limited treatment areas ( Gong et al, 2021 ). Mohammed et al (2018) studied the use of ADSC-Exos as adjunctive therapy to nonsurgical periodontal treatment.…”
Section: Clinical Translation Of Exosome Therapymentioning
confidence: 99%